Oxidation of Organic Sulfides by Imidazolium Fluorochromate: A Kinetic and Mechanistic Approach - Mathur, Lokesh; Choudhary, A.; Prakash, Om; K. Sharma, Pradeep (Asian Journal of Chemistry, 2014)
The oxidation of organic sulfides by imidazolium fluorochromate resulted in the formation of the corresponding sulfoxides. The reaction is first order with respect to imidazolium fluorochromate. A Michaelis-Menten type kinetics was observed with respect to the reactants. The reaction is catalyzed by toluene-p-sulfonic acid. The oxidation was studied in nineteen different organic solvents. An analysis of the solvent effect by Swain's equation showed that the both cation- and anion-solvating powers of the solvents play important roles. The correlation analyses of the rate of oxidation of thirty four sulfides were performed in terms of various single and multiparametric equations. For the aryl methyl sulfides, the best correlation is obtained with Charton's LDR and LDRS equations. The oxidation of alkyl phenyl sulfides exhibited a good correlation in terms of Pavelich-Taft equation. The polar reaction constants are negative indicating an electron-deficient sulfur centre in the rate-determining step. A mechanism involving formation of a sulphenium cation intermediate in the slow step has been proposed.